The psychology of criminal conduct: a consideration of strengths, weaknesses and future directions - Fortune, Clare-Ann (Psychology, crime & law, 2019)
Our understanding of the psychology of criminal conduct has progressed markedly in the last 30-40 years. We provide a brief overview of the seminal work of Andrews and Bonta, the Psychology of Criminal Conduct (PCC), and its four key components. As theory evaluation and revision is a crucial task in informing practice we consider some of the strengths and weaknesses of this approach. We then explore issues with the measurement, conceptualization and determination of dynamic risk factors (DRF). We argue that it is important to be open to critiquing such influential works as the PCC, as a deeper understanding of DRF will result in more effective assessment and treatment processes, and greater reductions in recidivism. This does not mean abandoning all we know about risk, it means enhancing our ability to locate the causes of problems and target these in interventions. Suggestions are made about developing models of human behavior that can depict the functions and inter-relationships of DRF across time and how improvements in the conceptualization, and explanatory depth, of DRF, may assist in the development of the PCC. These developments will ensure we provide the best interventions, with the most promising outcomes, that will benefit individuals and their community.